Symbolizm i funkcja Okna Pojawień w okresie amarneńskim - Kloska, Maria M. (Folia Praehistorica Posnaniensia, 2019)
During the reign of the Amarna spouses, giving gold necklaces to royal officials took place (almost always) from the so-called Window of Appearance. From them, Akhenaten and Nefertiti, often with princesses, honoured deserved and devoted dignitaries. The popularity of the Window of Appearance closely relates to the introduction of a new religious system introduced by Akhenaten and Nefertiti. According to the new religion, Akhenaten and Nefertiti were a pair of divine twins like Shu and Tefnut, who in the Heliopolitan theology, were the children of the god Atum – replaced by Aten in Amarna. The royal couple prayed to the main solar god, while their subjects prayed to the king and queen. Since Akhenaten performed the role of a priest through whom ordinary people could pray to the god, it was necessary to create a construction that would allow the king to meet with his subjects publicly. The Window of Appearance was such architectural innovation. It was crucial because the king was an intermediator between the people and the only right sun god, Aten. The Windows of Appearance were probably located in various places in Akhetaten, including the Great Palace, the King’s House, the North Palace, the Small Aten Temple and in the temples of the Sunshades of Re in the Kom el-Nana and Maru-Aten. The characteristic shape of the Window of Appearance often appears in the architecture and the art of the Amarna Period. The structure resembles the Axt hieroglyph, which is the morning sun rising between two hills. This symbol is a part of the name of the new capital Axt-itn – The Horizon of Aten.